Analysis and Evaluation of the Image of the University in the Context of the City-University Interaction - Bekebayeva, Mira; Kelesbayev, Dinmukhamed; Sadykov, Aripkhan; Kalykulov, Kuatbek; Yertayev, Yermek (International Review of Management and Marketing, 2024)
Institutional image is very important for universities and the importance of institutional image becomes clear when we consider it from the perspective of city-university interaction. If a university has a stronger institutional image, it will achieve great success in the academic world with its scientific research and publications, as well as gain an advantage in competition with many universities, and contribute to its integration with the internal and external environment. The purpose of this article, prepared in this context, is to assess the institutional image of Khoja Akhmet Yassawi International Kazakh-Turkish University (Akhmet Yassawi University) from the point of view of the residents of the city of Turkestan, where the university is located, and to study the impact of that institutional image. Within the framework of the research, the public assessment of the university’s educational, healthcare, socio-cultural and sports services, as well as the level of the university’s interaction with the city, were considered. In addition, variables such as characteristics of the organization, its appearance, management style and quality of service, which are effective in forming the institutional image, were considered and they were evaluated as components of the institutional image. At the end of the study, the current image of the university was analyzed, recommendations were made to the university management on obtaining a positive image, planning, implementing and monitoring its strategies. As a result of the research, it was found that the institutional image of the university is a good image in terms of perception, evaluation and opinions of Turkestan people. However, it was also known that the university could not fully communicate its activities to the target audience.